Strategi Pemanfaatan Media Sosial Instagram Feeds Pemerintah Kota Cirebon - Dhewo Djakti Abriantoro; Wiki Angga Wiksana (Bandung Conference Series: Public Relations, 2023)
Abstract. The Regional Government of Cirebon City, as one of the cities in West Java, has made Cirebon a "smart city", so in line with this, the use and use of social media is important in communicating and disseminating information to the public as well as feedback from the community to local government. Instagram @pemdakotacrb every time he spreads information, he always creates creative content and with communication that makes people interested in seeing this information. The purpose of this research is to find out how the social media utilization strategy of the Cirebon city government is Instagram feeds. With qualitative research methods using a case study approach. Data collection techniques used are interviews, observation, and literature studies, the internet, and documentation. The results of the study show (1) The content management process carried out by the Regional Government of Cirebon City through the Instagram account @pemdakotacrb has several stages, including preparing content and posting content. (2) The reason the Cirebon City Government uses Instagram is because Instagram social media is flexible, interactive and has many features that can be utilized to make it easier to interact with its followers (3) Posting Instagram feeds that have visual themes and colors according to the color of the logo they have, the color – the color has no special meaning in posting Instagram feeds, but the color is used based on the existing logo, so that their identity can be seen by comparing the color of the logo of the Cirebon City Government itself, but in this logo the choice of colors in the logo definitely has its own meaning. Abstrak. Pemerintah Daerah Kota Cirebon sebagai salah satu kota di Jawa Barat yang menjadikan Cirebon “smart city” maka sejalan dengan hal tersebut penggunaan dan pemanfaatan media sosial menjadi hal penting dalam berkomunikasi dan menyebarkan informasi bagi masyarakat begitu juga umpan balik dari masyarakat terhadap pemerintah daerah. Instagram @pemdakotacrb setiap menyebarkan informasi selalu membuat konten yang kreatif dan dengan komunikasi yang membuat masyarakat tertarik melihat informasi tersebut. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana strategi pemanfaatan media sosial instagram feeds pemerintah kota cirebon. Dengan metode penelitian kualitatif menggunakan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan studi kepustakaan, internet, dan dokumentasi.. Hasil penelitian menunjukan (1) Proses pengelolaan konten yang dilakukan oleh Pemerintah Daerah Kota Cirebon melalui akun Instagram @pemdakotacrb memiliki beberapa tahapan, di antaranya yaitu mempersiapkan konten dan memposting konten. (2) Alasan Pemerintah Daerah Kota Cirebon menggunakan Instagram yaitu karena media sosial instragram fleksible, interaktif dan banyak fitur yang bisa dimanfaatkan yang memudahkan berinteraksi dengan followersnya (3) Postingan feeds Instagram yang mempunyai tema visual dan warna sesuai dengan warna logo yang mereka miliki, warna – warna itu tidak ada makna khusus dalam postingan feeds Instagram namun warna tersebut digunakan berdasarkan logo yang ada, agar identitas mereka terlihat dengan membranding warna logo dari Pemda Kota Cirebon itu sendiri, namun dalam logo tersebut pemilihan warna dalam logo pasti memiliki makna tersendiri.